2019
DOI: 10.1016/j.antiviral.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, proof-of-concept clinical trial on repurposing chlorcyclizine for the treatment of chronic hepatitis C

Abstract: Background & Aims: Chlorcyclizine HCl (CCZ) is a piperazine-class antihistamine with antihepatitis C virus (HCV) activity in vitro and in vivo. In a first-in-humans study for HCV, we evaluated the antiviral effects and safety of CCZ±ribavirin (RBV), characterized pharmacokinetic (PK) and viral kinetic (VK) patterns, and provide insights into CCZs mode of action against HCV. Methods: Chronic HCV patients were randomized to CCZ (75mg twice daily) or CCZ+weightbased RBV (1000/1200mg daily) for 28 days. Therapy st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A small study involving CCZ treatment of 24 adult patients with a median HCV RNA load of 6.3 log IU/mL indicated that the drug used as monotherapy (2mg/kg x 28 days) produced no significant reduction in viremia (p= 0.69) [109]. However, 7/12 (58%) patients treated with CCZ+ ribavirin (RBV) had >3-fold decrease in HCV RNA.…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…A small study involving CCZ treatment of 24 adult patients with a median HCV RNA load of 6.3 log IU/mL indicated that the drug used as monotherapy (2mg/kg x 28 days) produced no significant reduction in viremia (p= 0.69) [109]. However, 7/12 (58%) patients treated with CCZ+ ribavirin (RBV) had >3-fold decrease in HCV RNA.…”
Section: Hepatitis C Virus (Hcv)mentioning
confidence: 99%
“…And in vivo studies further demonstrated its efficacy in inhibiting genotypes 1b and 2a HCV infection [ 10 ]. In addition, the results of a randomized proof-of-concept clinical trial showed that chlorcyclizine had some anti-HCV effects, and most notably in combination with ribavirin, a broad-spectrum antiviral agent [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…They previously demonstrated that CCZ shows promising efficacy for inhibiting HCV infection in mice and has a synergistic effect with multiple DAAs including ribavirin (RBV) in vitro, without significant cytotoxicity caused by drug interaction (He et al, 2015). However, in a recent small clinical trial (ClinicalTrials.gov number: NCT02118012), CCZ demonstrated limited anti-HCV effects, mostly in combination with RBV, although that may be due to a lack of genotype 2 infected patients in the trial (Koh et al, 2019).…”
mentioning
confidence: 99%